1992
DOI: 10.1523/jneurosci.12-08-03025.1992
|View full text |Cite
|
Sign up to set email alerts
|

The role of NMDA and non-NMDA excitatory amino acid receptors in the excitation of primate spinothalamic tract neurons by mechanical, chemical, thermal, and electrical stimuli

Abstract: The role of excitatory amino acids (EAAs) in the excitation of monkey spinothalamic tract (STT) neurons following activation of cutaneous primary afferent fibers by noxious and non-noxious stimuli was investigated. The responses of STT neurons to either NMDA or non-NMDA EAA ligands were blocked by infusion of specific antagonists through a microdialysis fiber into the region surrounding the cells. Our results show that blockade of non-NMDA receptors results in a nearly complete elimination of the responses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
130
0
4

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(143 citation statements)
references
References 64 publications
9
130
0
4
Order By: Relevance
“…In particular, the role of glutamate and NMDA receptors in spinal and supraspinal transmission, integration and modulation of both nociceptive and non nociceptive somatosensory signals is extensively documented (e.g. Dougherty et al 1992;Salt and Eaton, 1996). The reduction of paradoxical pain induced by ketamine may be a consequence of its action in the spinal dorsal horn and/or in the brain, particularly in the thalamus where there are numerous glutamate receptors, including the NMDA subtype (Salt, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the role of glutamate and NMDA receptors in spinal and supraspinal transmission, integration and modulation of both nociceptive and non nociceptive somatosensory signals is extensively documented (e.g. Dougherty et al 1992;Salt and Eaton, 1996). The reduction of paradoxical pain induced by ketamine may be a consequence of its action in the spinal dorsal horn and/or in the brain, particularly in the thalamus where there are numerous glutamate receptors, including the NMDA subtype (Salt, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In a human study, mechanical hyperalgesia evoked by intradermal capsaicin injection was also partially reversed by ketamine (Park et al, 1994). A range of inflammatory stimuli also produce NMDA receptor antagonist-sensitive increases in the mechanical responses of dorsal horn neurones (Schaible et al, 1991;Dougherty et al, 1992;Ren et al, 1992a;Neugebauer et al, 1993) and of spinal reflexes (Woolf & Thompson, 1991;Ma & Woolf, 1985). However, mechanical hyperalgesia evoked by peripheral neuropathy in rats was not affected by treatment with dextrorphan, an NMDA receptor ion channel blocker, although thermal hyperalgesia was reversed in the same study (Tal & Bennett, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effect of NMDA receptor antagonists on mechanical hyperalgesia in animals is less clear cut, since whilst Ren & Dubner (1993) found that blockers of the NMDA receptor ion channel attenuated mechanical hyperalgesia evoked by inflammation, others have found that NMDA receptor antagonists had no effects on mechanical hyperalgesia evoked by neuropathy (Tal & Bennett 1993) and that intrathecal administration of NMDA provokes thermal but not mechanical hyperalgesia (Mellor et al, 1993). However, in electrophysiological studies, NMDA receptor antagonists reverse the increased mechanical responsiveness of spinal neurones induced by arthritis (Schaible et al, 1991;Neugebauer et al, 1993), by intradermal capsaicin (Dougherty et al, 1992), or by intraplantar injection of Freund's adjuvant (Ren et al, 1992a) and also reduce the hyper-reflexia to mechanical stimuli induced by mustard oil or bradykinin (Woolf & Thompson, 1991;Ma & Woolf, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Basic research from this field has generated enormous information that has contributed major progress in understanding the neural mechanisms of neuropathic pain. To date, however, studies on the role of the central glutamatergic system in neuropathic pain have been focused mainly on the modulation of glutamate receptors and the associated intracellular events (Dougherty and Willis, 1991;Dubner, 1991;Wilcox, 1991;Dougherty et al, 1992;Mao et al, 1992aMao et al, ,b, 1995Yamamoto and Yaksh, 1992;Malmberg et al, 1997;Woolf and Mannion, 1999;Guo et al, 2002).…”
Section: Contributions To the Central Mechanisms Of Neuropathic Painmentioning
confidence: 99%
“…An increase in neuronal excitability within the CNS may be initiated and maintained after excessive activation of central glutamate receptors by their endogenous ligands, namely glutamate and aspartate. To date, much effort and progress have been made in investigating the role of glutamate receptor activation and subsequent intracellular events in the pathogenesis of neuropathic pain (Dougherty and Willis, 1991;Dubner, 1991;Wilcox, 1991;Dougherty et al, 1992;Mao et al, 1992aMao et al, ,b, 1995Yamamoto and Yaksh, 1992;Malmberg et al, 1997;Woolf and Mannion, 1999;Guo et al, 2002). Little has been known about the role of regulating endogenous ligands of glutamate receptors in the central mechanisms of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%